DC-Link Capacitor-Current Ripple Reduction in DPWM-Based Back-to-Back Converters - Tcai, Anatolii; Shin, Hye Ung; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2018)
This paper proposes an improved offset selection method for discontinuous-pulse-width-modulation (DPWM)-based back-to-back converters to reduce dc-link current ripple. DPWM is introduced to power converters to diminish the stress on power transistors and prolong their lifespan. However, when using the DPWM method, the dc-link current ripple is increased in nonswitching regions of the power transistors. Moreover, in DPWM-based back-to-back converters, the dc-link current ripple reaches its maximum when the two transistors of both inverters are clamped in opposite directions. Therefore, the dc-link capacitors endure more stress, resulting in decreased life duration. To overcome this issue, the switching method should consider the clamping periods, when the current ripple increases. This can be achieved by modifying the DPWM offset, so that the clamping states of both converters are matched. The effectiveness of the proposed method is confirmed by both simulation and experimental results.
Keywords: Back-to-back; Current-ripple reduction; DC links; DPWM; Power conversion; Voltage source inverter; Back to back; current ripple reduction; dc link; discontinuous pulse width modulation (DPWM); voltage-source inverter